Stability of Zener order in martensite: an atomistic evidence. (15th March 2021) - Maugis, Philippe; Connétable, Damien; Eyméoud, Paul
Highlights: The energetic stability of Zener order in Fe-C supersaturated alloys is confirmed by SQS-DFT calculations. The origin of Zener ordering is the long-range strain-induced carbon–carbon elastic interaction. Applied tensile and compressive stresses both stabilise Zener order. Graphical abstract: Abstract: Martensite is a supersaturated solid solution of carbon in body-centered iron wherein interstitial carbon atoms preferentially occupy a single octahedral sublattice. Despite a century of research, the mechanism of this long-range ordering is still a subject of debate. Recently, Zener's theory of ordering was challenged both experimentally and theoretically. In an attempt to settle the controversy, we investigated by density functional theory the ground states of Fe-C configurations having various degrees of order. We conclude that the fully Zener-ordered configurations are always the most stable energetically, thus confirming Zener's theory. Comparison with mean-field elasticity and Ising-type modelling supports the elastic origin of Zener ordering.